Clinical Characteristics and Outcome of Laser Photocoagulation for The Treatment of Retinal Hole/Break in Preventing Retinal Detachment at Jakarta Eye Centre (2011-2015) - Supanji Supanji; Waldensius Girsang; Soedarman Sjamsoe; Elvioza Elvioza (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Background: It is almost a consistent recognition that the retinal detachment associated with retinal hole/breaks accounts for some cases of retinal detachments. However, the treatment of retinal hole/breaks without retinal detachment remains controversial. This retrospective study is designed to evaluate the prophylactic effect of laser photocoagulation for the treatment of retinal hole/breaks in order to prevent retinal detachment. Method: Eighty nine eyes of 85 patients with retinal hole/breaks were included in this study. Data is taken from medical record with the requirement of full follow-up for a year. They all were treated with laser photocoagulation around the hole/breaks margin. The average visual acuity of before and after treatment was compared. Furthermore, the laser photocoagulation characteristic (wavelength, power, spot size, exposure time) is measured. Results: The success rate of laser photocoagulation to prevent retinal detachment was 96.6% (86/89). The progression rate to retinal detachment was account for only 3.4% (3/89) of patient getting the laser photocoagulation treatment. The average best corrected visual acuity (BCVA) at 1 year follow up was 0.91 + 0.16, while the average BCVA before photocoagulation was 0.93 + 0.12. The average amount of laser to treat was 638.1 + 443.99 in range of 56 – 1863 spot and the laser photocoagulation is done on the day of diagnosis for 96.6% cases. Conclusion: Photocoagulation reduce the rate of retinal detachment of retinal hole/breaks without the impairment of visual acuity outcome. Therefore, laser photocoagulation is relatively an effective and safe method for the treatment of retinal hole/breaks to prevent retinal detachment.